The Virtual Human Platform: Simplifying the Use of Virtual Characters - Knöpfle, Christian; Jung, Yvonne (International Journal of Virtual Reality, 2006)
In this paper, we will explain our approach to create and animate virtual characters for real-time rendering applications in an easy and intuitive way. Furthermore we show a way how to develop interactive storylines for such real-time environments involving the created characters. We outline useful extensions for character animation based on the VRML97 and X3D standards and describe how to incorporate commercial tools for an optimized workflow. These results were developed within the Virtual Human project. An overview of the project is included in this paper